Preventing Degradation of the Quality of Visual Information in Digital Signage and Image-Sensor-Based Visible Light Communication Systems - Hiraku Okada; Sho Sato; Tadahiro Wada; Kentaro Kobayashi; Masaaki Katayama (IEEE Photonics Journal, 2018)
In this paper, we propose an image-sensor-based visible light communication (IS-VLC) system that provides visual information in digital signage used for advertisements. One important issue of IS-VLC systems is the deterioration of visual information while transmitting the data information. Human eyes are sensitive to luminance but not to color difference; therefore, we propose the modulation of color difference. We evaluate the performance of the proposed system in terms of both the quality of visual information and communication quality of data information, and clarify the effectiveness of the proposed system.